Comparison Between Phenotypic Bead Assay and Single Antigen Bead Assay for Determining Specificity of HLA Antibodies in Kidney Transplant Waiting List - Duangtawan Thammanichanond (2020)
© 2020 Elsevier Inc. Objectives: The determination of unacceptable antigens in patients on kidney transplant waiting list is a critical laboratory investigation in sensitized patients. The Luminex single antigen bead (SAB) assay has high sensitivity and accuracy. However, several countries have not yet implemented SAB testing for waitlisted patients because of limited financial resources. In Thailand, specificities of HLA antibodies are identified by using a phenotypic bead assay. The aim of this study was to evaluate the performance of the phenotypic bead assay for determining HLA antibody specificities when compared with the SAB assay. Methods: A total of 254 sera from patients awaiting kidney transplantation were included. Of 254 sera, 206 and 171 were positive for HLA class I and II antibodies, respectively. Antibody specificities of sera that were tested with both phenotypic and SAB assay were analyzed. The performances of the phenotypic bead assay were compared with those of the SAB assay as the gold standard by using estimation of pooling sensitivity, specificity, and accuracy. Results: The sensitivity, specificity, and accuracy of the phenotypic bead assay for determining HLA class I antibodies was 53.9%, 93.0%, and 78.1%, respectively. The sensitivity, specificity, and accuracy of the phenotypic bead assay for determining HLA class II antibodies were 57.3%, 94.9%, and 81.4% respectively. Conclusion: In waitlisted kidney transplant patients, the phenotypic bead assay had high specificity and moderate accuracy when compared with the SAB assay. However, the low sensitivity of the test suggests that the use of the phenotypic assay for determining HLA specificities should be applied with caution in sensitized patients.